Students’ Perceptions of Using Kahoot in Arabic Language Learning: تصورات الطلاب عن استخدام كاهوت في تعلم اللغة العربية - Afifah, Niswatul; Jannah, Rauzatul (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2024)
As technology continues to advance and integrate into education, the Kahoot application has emerged as a valuable tool for technology-based learning. Hence, this study explores the perceptions of Arabic language education students at IAIN Lhokseumawe regarding the use of Kahoot in their learning process. The research aims to assess students' responses to Kahoot in Arabic language learning to determine whether their perception is positive or negative. This study follows a descriptive quantitative approach, using questionnaires as the primary data collection method. The research population includes all Arabic language education students at IAIN Lhokseumawe, with a sample of 61 students selected based on the Slovin formula. The findings indicate that students hold a highly positive perception of Kahoot in Arabic language learning, with an overall approval rating of 92% and an average score of 4.61. This result is based on five key perception indicators which are student engagement: 93% (average score: 4.68), effectiveness: 92% (average score: 4.60), interest in the application: 93% (average score: 4.69), student learning interest: 92% (average score: 4.62) and student motivation: 90% (average score: 4.52). These results suggest that Kahoot is well-received and contributes positively to students' learning experiences in Arabic language education at IAIN Lhokseumawe. The findings imply that Kahoot effectively enhances student engagement, motivation, and interest in Arabic language learning, suggesting that technology-based tools should be more widely integrated into language education.